2017
DOI: 10.14416/j.appsci.2017.10.s14
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and times by hydrothermal carbonization process from sawdust and bagasse for carbon materials supporter

Abstract: Carbon supporter from biomass has been fabricated by hydrothermal carbonization due to this process changes the structure of lignocellulose including cellulose, hemicellulose and lignin. The applications from carbon support are gaining in importance due to decreasing supply of fossil fuels and growing environmental concerns. Hydrothermal carbonization process was used to upgrade biomass such as sawdust and bagasse varying temperature at 160 to 200 o C and varying times at 4 to 24 hr with deionized water 120 ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…The result of the FTIR analysis showed that lignin content was still high and only fractionally reduced, while cellulose and hemicellulose content was very limited. This finding was in accordance with the research finding of Sumtong et al (2017), which stated that lignin content was only slightly decomposed while cellulose and hemicellulose were almost entirely decomposed in hydrothermal process.…”
Section: Fig 4 Ftir Spectra Of Bamboo Charcoal and Bamboo Activated Carbonsupporting
confidence: 93%
“…The result of the FTIR analysis showed that lignin content was still high and only fractionally reduced, while cellulose and hemicellulose content was very limited. This finding was in accordance with the research finding of Sumtong et al (2017), which stated that lignin content was only slightly decomposed while cellulose and hemicellulose were almost entirely decomposed in hydrothermal process.…”
Section: Fig 4 Ftir Spectra Of Bamboo Charcoal and Bamboo Activated Carbonsupporting
confidence: 93%